2014
DOI: 10.1182/blood-2013-07-517086
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the major factor VIII binding region on von Willebrand factor

Abstract: Key Points• The high-resolution structure of the complex disulfidebonded TIL9E9 (D9) region of VWF is presented.• The major factor VIII binding site is localized around a flexible region on the TIL9 domain.Although much of the function of von Willebrand factor (VWF) has been revealed, detailed insight into the molecular structure that enables VWF to orchestrate hemostatic processes, in particular factor VIII (FVIII) binding and stabilization in plasma, is lacking.Here, we present the high-resolution solution s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 49 publications
4
60
0
Order By: Relevance
“…The dimensions of the handle are ;20Å 3 ;60Å, in agreement with the dimensions of the D9 domain structure determined by nuclear magnetic resonance spectroscopy. 9 This observation indicates that D3 forms the ovoid density (;30Å 3 ;60Å) and homodimerizes along the symmetry axis, consistent with a previous report identifying intermolecular disulfide bonds located at the C-terminus of the D3 domain (C1099-C1099 and C1142-C1142) that coordinate dimerization of VWF fragments comprising the D9D3 domains. 4 To confirm this interpretation of the relative disposition of D9 and D3 domains, we labeled [D9D3] 2 with an Ag-binding fragment (Fab) directed against the FLAG epitope tag located at the D3 C-terminus.…”
Section: Resultssupporting
confidence: 90%
“…The dimensions of the handle are ;20Å 3 ;60Å, in agreement with the dimensions of the D9 domain structure determined by nuclear magnetic resonance spectroscopy. 9 This observation indicates that D3 forms the ovoid density (;30Å 3 ;60Å) and homodimerizes along the symmetry axis, consistent with a previous report identifying intermolecular disulfide bonds located at the C-terminus of the D3 domain (C1099-C1099 and C1142-C1142) that coordinate dimerization of VWF fragments comprising the D9D3 domains. 4 To confirm this interpretation of the relative disposition of D9 and D3 domains, we labeled [D9D3] 2 with an Ag-binding fragment (Fab) directed against the FLAG epitope tag located at the D3 C-terminus.…”
Section: Resultssupporting
confidence: 90%
“…48,50 A VWF-D9 solution structure 55 ( Figure 3), as well as modeling based on single-particle electron microscopy of complexes formed by FVIII and VWF-D9D3 domains, 56,57 have allowed further analysis of the FVIII-VWF interface and of VWF-D9 mutations associated with reduced FVIII-VWF affinity and type 2N VWD. These studies have shown that the positively charged VWF-D9 surface is probably a binding site for FVIII-ap.…”
Section: Fviii and Vwf Structural Biologymentioning
confidence: 99%
“…The structure of D9 shows how E' extends the highly dynamic TIL9 module away from the D3 assembly to bind FVIII ( Figure 1J). 7 von Willebrand C (VWC) modules have 2 disulfide-rich subdomains ( Figure 1H). 8,9 The E module of D assemblies is related to the first VWC subdomain.…”
mentioning
confidence: 99%
“…8,9 The E module of D assemblies is related to the first VWC subdomain. 2,7 The 6 tandem VWC modules extend VWF length and give it flexibility (Figure 2). Platelet integrin a IIb b 3 binds an RGD motif in the VWC4 module 2 ( Figure 1A).…”
mentioning
confidence: 99%